Influence of cyclic compressive forces in bone tissue engineering - Ravichandran, Akhilandeshwari (2017)
Bone is one of the most transplanted tissues in the world and the current clinical strategies are unable to meet the growing demand for bone grafts. Therefore, bone tissue engineering (BTE) has become one of the potential alternatives to produce highly cellularized and mineralized bone grafts to meet the growing demand in clinics. Despite the advances in BTE, the current in vitro methods have not successfully generated viable, voluminous and mineralized 3D constructs. In this thesis, we hypothesized that application of physiologically relevant mechanical forces would enable generation of highly osteogenic constructs. Influence of mechanical stimulation and fluid flow on in vivo bone remodeling has been extensively studied in the past. However, there is lack of a systemic study to understand the effect of physiological strains on in vitro bone formation. To fill this gap, we developed a multi-chamber compression bioreactor system to apply cyclic compressive forces on cell loaded scaffolds under controlled environment to evaluate osteogenesis and mineralization of cellular grafts. A parametric optimization study conducted by applying a range of strains on Mesenchymal Stem Cells (MSC) seeded Polycaprolactone-β-Tricalcium Phosphate (PCL-TCP) scaffolds demonstrated that physiologically relevant strains resulted in enhanced osteogenic differentiation. Further, a long term study with optimized strain values indicated cyclic compressive loading induced upregulation of osteogenic gene expression. Osteogenic enzyme activity was also highly elevated by the end of two weeks in comparison to the static cultures. These results suggested the potential of cyclic compressive loading for generating mineralized tissues.